Thermal nondestructive testing of composites and multilayered. Articles. 2. New procedures and thermogram processing; Defektoskopiya; № 10 - Vavilov V. P. Vladimir Platonovich (1993, 1993)
In modern experiments on thermal testing, infrared imagers have found the most widespread application. These devices make it possible to obtain thermal patterns in time and space regions with subsequent synthesis of special images which can be calibrated in thermal characteristics or flaw parameters. Computer processing of the images provides a possibility to suppress the noises caused by structural irregularities, low-quality heating, or background radiation.